2016
DOI: 10.1186/s41240-016-0024-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding frequency, water temperature, and stocking density on the growth of river puffer Takifugu obscurus reared in a zero-exchange water system

Abstract: The effects of daily feeding frequency (Exp I), water temperature (Exp II), and stocking density (Exp III) on the growth of river puffer, Takifugu obscurus, juvenile fish of 10 and 40 g in body weight were examined to develop effective techniques to produce river puffer in a non-exchange water system. In Exp I, fish were fed commercial floating feed with 45 % protein one to five times per day to apparent satiation each by hand daily for 8 weeks at 25°C. In both the 10-and 40-g size groups, the final body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…The average values of water quality parameters such as temperature, transparency, pH, dissolved oxygen, nitrite, nitrate, and ammonia monitored throughout the trials were considered as suitable for the survival, normal growth, as well as good general physiology of O. niloticus. These values were in accordance with the findings of Yoo and Lee, 2016, Makori et al 2017and Nyadjeu et al (2018 and could partially justify the absence of mortality observed throughout the study, coupled with experimental fish's apparent good health observed through the results on both the growth and feed utilization.…”
Section: Discussionsupporting
confidence: 90%
“…The average values of water quality parameters such as temperature, transparency, pH, dissolved oxygen, nitrite, nitrate, and ammonia monitored throughout the trials were considered as suitable for the survival, normal growth, as well as good general physiology of O. niloticus. These values were in accordance with the findings of Yoo and Lee, 2016, Makori et al 2017and Nyadjeu et al (2018 and could partially justify the absence of mortality observed throughout the study, coupled with experimental fish's apparent good health observed through the results on both the growth and feed utilization.…”
Section: Discussionsupporting
confidence: 90%
“…This suggested that the growth performance of the sh in the 1.10 kg and 1.65 kg per tank stocking densities was better than that of the other groups with the same feeding frequency. In other words, feeding frequency and stocking density in uenced the growth performance of this species, which was consistent with previous studies [27,28]. The poor growth performance observed in the high stocking density was likely due to crowding stress [29].…”
Section: Discussionsupporting
confidence: 90%
“…Taking experiment needs and the suitable culture density of juvenile T. fasciatus into consideration [28], a total of 120 juvenile T. fasciatus (13 ± 1.76 cm in length, 22 ± 2.85 g in weight), supplied from Zhongyang Group Co., Ltd. (Jiangsu Province, China), were randomly transferred to six aquaria with biofiltered water recirculation systems (equipped with cooling and heating functions; volume 200 L; flow rate 5 L/min), and were divided into the control group (G1, G2 and G3; total of 60 individuals; 2.2 ± 0.3 g/L) and the experimental group (Ga, Gb and Gc; total of 60 individuals; 2.2 ± 0.3 g/L). These individuals were acclimated at 26 ± 1 °C for 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the pufferfish is also popular in Korea [26] and Japan [27]: pufferfish sashimi is widely known. As a kind of warm-water fish [28], T. fasciatus has an optimum growing temperature between 23 °C and 32 °C [29]. However, in farms as well as rivers, the water temperature in winter is far below that optimal growth temperature, which causes massive deaths of T. fasciatus and leads to large economic losses.…”
Section: Introductionmentioning
confidence: 99%